Implementation of Web Service Fingerprint Attendance Machine on Employee Attendance Information System - Saracen Foust Badr; Muhammad Nasir (Journal of Information System and Informatics, 2022)
The OKI District Population and Civil Registration Service have implemented the employee attendance information system by utilizing a fingerprint machine. This system is quite helpful in recording employee attendance properly. However, several obstacles are found in the implementation of the system. Namely, calculating the attendance percentage is still done manually because the data must be further processed using additional applications. Based on these obstacles, this study aims to implement web service technology using the protocol SOAP to integrate the system currently used. The system will automatically download fingerprint machine data and process it into attendance percentage reports, so that it can be more optimal and increase efficiency. The data obtained will be used by the staffing department, including one of the factors for measuring employee performance and determining Additional Employee Income (TPP).